1994
DOI: 10.1254/jjp.66.247
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes of Cholinergic Markers in the Rat Brain

Abstract: ABSTRACT-To evaluate whether any degenerative changes affect the brain cholinergic systems during natural aging, we compared various cholinergic biochemical markers (number of muscarinic receptors, mAChR; choline acetyltransferase activity, ChAT; acetylcholinesterase activity, AChE; and sodium-de pendent high affinity choline uptake) in the cortical (CR) and subcortical (SS) regions of the brains of aged (24 month) and young (2 month) rats. Using [3H]-quinuclidinyl benzilate ([3H]-QNB) as the ligand of muscari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 48 publications
(51 reference statements)
2
11
1
Order By: Relevance
“…Because it is well-known that the functioning cholinergic system can be damaged by cerebral ischemia (14), we compared various cholinergic biochemical markers (mAChR and ChAT activity) in the cortex, hippocampus and striatum of the brains of aged (24 month) and young (6 weeks) rats treated with permanent 2VO. We previously reported that the investigation of brain cholinergic systems in aged control rats could provide useful information pertaining to age and age-related disorders in humans (9,10). However, in this study, ChAT activity and the number of mAChR in aged 2VO rats decreased nearly 10-20% as compared with those in aged control rats.…”
Section: Choline Acetyltransferase Activity Assaycontrasting
confidence: 58%
See 1 more Smart Citation
“…Because it is well-known that the functioning cholinergic system can be damaged by cerebral ischemia (14), we compared various cholinergic biochemical markers (mAChR and ChAT activity) in the cortex, hippocampus and striatum of the brains of aged (24 month) and young (6 weeks) rats treated with permanent 2VO. We previously reported that the investigation of brain cholinergic systems in aged control rats could provide useful information pertaining to age and age-related disorders in humans (9,10). However, in this study, ChAT activity and the number of mAChR in aged 2VO rats decreased nearly 10-20% as compared with those in aged control rats.…”
Section: Choline Acetyltransferase Activity Assaycontrasting
confidence: 58%
“…We these data should aid in establishing a model of senile also investigated the effect of long-term administration dementia that could be used to investigate potentially of bifemelane on cholinergic markers in aged 2VO rats; therapeutic drugs (9,10). This model, however, employbifemelane is known to be an effective treatment for ed rats that were simply aged, not true models of senile cerebrovascular disease in clinical trials as well as in dementia.…”
mentioning
confidence: 99%
“…The basal forebrain cholinergic (BFC) system is particularly vulnerable during aging (Yufu et al 1994;Smith and Booze 1995). One structure adversely affected by the loss of BFC system integrity is the hippocampus (De Lacalle et al 1994).…”
mentioning
confidence: 99%
“…An age-related decline in AChE activity was reported in all brain regions (Michalek et al 1989;Bisso et al 1991). Decreased AChE activity observed in the cerebral cortex of 90 weeks old control group suggests a loss of postsynaptic enzyme activity during ageing (Sirvio et al 1988;Yufu et al 1994). Hyperglycaemia caused significant increase in AChE activity of both 7 and 90 weeks old rat groups, whereas insulin administration reversed this effect.…”
Section: Discussionmentioning
confidence: 88%
“…In our present study on muscarinic M1 receptor binding using [ 3 H]QNB with pirenzepine, we found that M1 receptor number decreased significantly in the cerebral cortex of control old rats compared to the young rats with a significant increase in the affinity. Total specific binding sites for the muscarinic antagonist, L-QNB showed a decline with age (Briggs et al 1982) and age-related increase in the affinity of mAChRs was observed in the cortical regions of rats (Yufu et al 1994). Studies using selective M1 antagonist, [ 3 H]-pirenzepine ([ 3 H]PZ) showed decreased receptor density in the cortex of aged rats compared to young rats (Schwarz et al 1990;Ehlert and Tran 1990).…”
Section: Discussionmentioning
confidence: 99%